Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1096/fj.201601234r
|View full text |Cite
|
Sign up to set email alerts
|

Timing of caloric intake during weight loss differentially affects striatal dopamine transporter and thalamic serotonin transporter binding

Abstract: Recent studies have shown that meal timing throughout the day contributes to maintaining or regaining weight after hypocaloric diets. Although brain serotonin and dopamine are well known to be involved in regulating feeding, it is unknown whether meal timing during energy restriction affects these neurotransmitter systems. We studied the effect of a 4 wk hypocaloric diet with either 50% of daily calories consumed at breakfast (BF group) or at dinner (D group) on hypothalamic and thalamic serotonin transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…The subjects were scanned after an overnight fast and pretreated with potassium iodide for thyroid blockade of free radioactive iodide. For scanning, the Inspira HD system was used, a brain-dedicated tomographic SPECT scanner (Neurologica, Boston, MA, USA), and an acquisition protocol as previously described (slice thickness 4 mm and acquisition time 180 s/slice) [ 71 ]. All the scans were reconstructed in 3D mode and corrected for attenuation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects were scanned after an overnight fast and pretreated with potassium iodide for thyroid blockade of free radioactive iodide. For scanning, the Inspira HD system was used, a brain-dedicated tomographic SPECT scanner (Neurologica, Boston, MA, USA), and an acquisition protocol as previously described (slice thickness 4 mm and acquisition time 180 s/slice) [ 71 ]. All the scans were reconstructed in 3D mode and corrected for attenuation.…”
Section: Methodsmentioning
confidence: 99%
“…To determine SERT binding in the thalamus and hypothalamus and DAT binding in the striatum, a region of interest (ROI) analysis was conducted as previously described [ 71 ] ( Figure 1 A). Striatal and thalamic masks were obtained from individual T1-weighted MRI scans using FreeSurfer (version 5.3.0.)…”
Section: Methodsmentioning
confidence: 99%
“…The ENC-DAT control database [ 3 ] as implemented in BRASS was used as a reference template and for region definition. An independent sample of healthy subjects scanned on the InSPira was used to assess if patient’s striatal ratios fell within the normal range (only available for InSPira data) [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…In routine practice, the majority of neuro SPECT studies within the Academic Medical Center consist of dopamine transporter (DAT) SPECT imaging [ 4 6 ]. DAT imaging with [ 123 I]FP-CIT is an established diagnostic tool to detect loss of the dopaminergic nigrostriata pathway, a hallmark of Parkinson’s disease (PD).…”
Section: Rationalementioning
confidence: 99%
“…This effect was not observed with other hypercaloric diets, indicating a role for diet composition in mediating these effects. Meal timing may be similarly important: obese subjects in a hypocaloric diet intervention study, who consumed most calories at breakfast, had increased thalamic serotonin and striatal dopamine transporter availability, whereas those, who consumed calories at dinner, had decreased availability of both transporters [242]. We have also shown that striatal D2/3R availability is reduced in obese women, but partially reversible after bariatric surgery-induced long-term weight loss [243]; this suggests that obesity may, in fact, cause the observed changes in the dopamine system.…”
Section: Cause and Effectmentioning
confidence: 99%